การพัฒนาระบบแนะนำหนังสือที่เกี่ยวข้องกับการสืบค้นสารนิเทศห้องสมุดโดยใช้เทคนิคอะไพออริอัลกอริทึม - สุทธิพงศ์ มณีรัตน์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objective of this independent study was developed the book recommendation for library information using apriori algorithm. Association rule was a type of data mining using apriori algorithm for creating association rules of keywords of books in Faculty of Science Library. The system could recommended keywords of books that relate to keywords of books searched by users. For this study, the researcher found the association rules of keywords of books in computer and technology field using apriori algorithm and could develop the book recommendation for library information. The results show that Faculty of Science Library has more potential services to the users.